Analisis Kelengkapan LKPD sebagai Media Pembelajaran Matematika Peserta Didik - Anita Setiyaningsih; Muhammad Ridlo Yuwono; Septiana Wijayanti (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2022)
This research was conducted with the aim of analyzing the LKPD used in delivering geometry transformation material for class XI SMK Negeri 4 Klaten. This study aims to analyze the completeness of Student Worksheets (LKPD) as a medium for learning mathematics. This research is a type of descriptive qualitative research. The method used in this research is the method of interviews and document review. The instruments used were interview guidelines and document review sheets. Based on the results of the analysis, information was obtained that the percentage of completeness of the components of the LKPD for geometry transformation material for class XI SMK Negeri 4 Klaten was 50%. Components that have not been included in the LKPD include LKPD objectives, apperceptions, contextual initial problems, overall conclusions, and problem solving. So it can be concluded that the LKPD is not classified as a good LKPD.